Representation of a Scientific Supervisor in Internet-Memes - N. V. Stepanova; M. S. Sigaeva (Дискурс)
Introduction. The purpose article is to consider the representation of the image of a  scientific supervisor based on Internet memes containing a multimodal metaphor. The  relevance of the topic is due to the growing interest of the interdisciplinary scientific  community in the study of the Internet meme as a social, linguistic, psychological  phenomenon of interpersonal communication. The scientific novelty of the work is  determined by the fact that until now there have been no attempts to study the  representation of the academic community from the perspective of the theory of conceptual  metaphor using the material of Internet memes. Methodology and sources. The methodological basis of the study was the works of  linguists and cognitive scientists J. Lakoff, M. Johnson, R. Dawkins, V. Aldrich, Ch. Forsville,  B. Dancygier and L. Vandelanotte. The concept of visual metaphor and multimodality is  defined, the role of multimodal metaphor in Internet discourse is described, the features of  the functioning of multimodal metaphor are revealed. The material for the study was  Internet memes representing various aspects of interaction in the academic environment.  To systematize the units, a continuous sampling method was used, along with  pragmalinguistic, contextual and semantic analysis. Results and discussion. The Internet memes containing a multimodal metaphor that  represents the image of a scientific supervisor and illustrates the relationship between  graduate students and their mentors were found and analyzed in the paper. To select the  material, a search containing the keywords “scientific supervisor”, “Phd student”, “advisor”  was performed. The sources of the memes were the podcasts “The Struggling Scientists”,  “The Meming Phd”, “High impact PhD memes”. By selecting keywords, 85 Internet memes  were identified in which metaphorical transfers of the above images were found. Based on  the data obtained, 4 metaphorical models that most clearly illustrate the relationships  between the supervisor and the student were proposed. Conclusion. The study showed that multimodal metaphor is an integral part of modern  Internet communication and is an effective way of influencing the addressee. Internet  memes representing the image of a scientific supervisor were analyzed and systematized;  4 metaphorical mappings (“Scientific supervisor is a loving/caring parent”, “Scientific  supervisor is a Jedi”, “Scientific supervisor is a monster/maniac”, “Scientific supervisor is a  bad boss”) are highlighted and described. It was revealed that the considered Internet memes are characterized by the replacement of the verbal component with a non-verbal  (graphic) one in the target domain or in the source domain. The studied metaphorical  models reflect the most pressing problems of the academic community. The expressiveness  of the metaphor used is achieved through the use of movie characters in the source domain  or target domain. The metaphorical potential of Internet memes as semantic-semiotic units  of Internet discourse is undoubtedly a promising area for further study.